Official classification, affirmative action, and self-identification: Hui-Han biethnic college students in China. Issue 2 (4th March 2022) - Lu, Xiang
ABSTRACT: The existing literature on the self-identity of multiethnic people focuses on Western countries where mixed identities have been normalised in census-taking. It remains unknown how multiethnic people identify themselves in countries where ethnic classification is exclusive and rigid and ethnicity is a mainly ascriptive legal category. Based on in-depth interviews with twenty Hui-Han biethnic college students in China, this article shows how official ethnic classification and affirmative action shape these people's self-identification. Most respondents identify themselves as Hui regardless of their cultural practices, as their parents registered their official ethnicity as Hui and they have internalised this identity. The multiethnic background is more frustrating for students at China's special 'universities for ethnicities' because ethnicity is a salient topic on campus and they experience more expectations to behave like Hui. Many respondents have an essentialist understanding of ethnicity and express unsupportive attitudes towards institutionalising mixed identities.